Evaluation of Natural potentials and Challenges of Land for Agricultural Activities in Fereydounshahr County - Hedayat Nouri; Ameneh Jovzi khamesluei (نشریه جغرافیا و برنامه‌ریزی, 2019)
Study and recognition of the capabilities of geographic regions to create the systematic scientific fields to achieve better use of available resources for useful and sustainable agriculture development is necessity. The mountain structure of Fereydounshahr has been increase the important of geographical spaces of this field from the point of view of rural development and agriculture.  Therefore, the main approach in this research is identifying and introducing the capabilities and limitations associated with land level for agriculture activities in the study field. This research could be part of a comprehensive land capability plan for sustainable agriculture development in field. In this study, the evaluation of land potential and the preparation of potential determination maps through the Geographic information system GIS based on the multi-criteria decision-making analytical approach (MCDM) has been carried out. Hierarchical analytic process (AHP) to weigh the criteria, and finally, weighted linear combination (WLC) method has also been used to integrate maps in order to achieve this result. The parameters were used in this study are topography including a digital elevation model and slope, soil characteristics including soil depth, soil texture, and soil gravel, as well as land use and land coverage. The results of the evaluation of the agricultural ability of the county show that 6.25% of the area is suitable, 6.15% of the land is relatively suitable, 12.88% of the land area is slightly suitable and 6. 88 % of the area is almost unsuitable. This is while 67.84% of the area is in full constraint for agricultural activity.